1987
DOI: 10.1037/0882-7974.2.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological problem-solving skills in the elderly.

Abstract: This article describes the performance of a representative sample of 110 participants aged from 65 to 75 years. Participants completed the Trail-Making Test, Tactual Performance Test, and Booklet Category Test. Results confirmed that previously established cutoff scores used to determine impairment are not appropriate for this age group. Significant sex differences were found for the Tactual Performance Test and Booklet Category Test. Mean scores presented in this article provide useful normative standards for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
(13 reference statements)
1
15
1
Order By: Relevance
“…Schaie, Maitland, Willis, and Intrieri (1998) found that males retain superior spatial rotational abilities into the eighties and perform better than females in later years on the water-level task. This is consistent with a male advantage seen among older samples on Block Design (Portin et al, 1995), Trails A (Portin et al, 1995) and Trails B (Ernst, 1987). However, Robert and Tanguay (1990) suggest that the male advantage on the Rod and Frame test may not persist into old age.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Schaie, Maitland, Willis, and Intrieri (1998) found that males retain superior spatial rotational abilities into the eighties and perform better than females in later years on the water-level task. This is consistent with a male advantage seen among older samples on Block Design (Portin et al, 1995), Trails A (Portin et al, 1995) and Trails B (Ernst, 1987). However, Robert and Tanguay (1990) suggest that the male advantage on the Rod and Frame test may not persist into old age.…”
supporting
confidence: 86%
“…Further, although current results replicated findings in studies reporting males retaining superior spatial rotational abilities in general, it did not do so on studies finding male superiority for completing Trails A (Portin et al, 1995) and Trails B (Ernst, 1987). This lack of replication of certain non-verbal domains may be due to the obfuscating influence of common variance among the measures (discussed below).…”
contrasting
confidence: 72%
“…[11][12][13][14][15][16][17][18][19][20] There is inconsistency in previous reports regarding the effect of educational level on TMT-A times.…”
Section: Disucussionmentioning
confidence: 77%
“…In contrast, conclusions regarding the influence of educational level on the TMT have been inconsistent between studies; some studies have shown that educational level affects both parts of the TMT, [11][12][13][14]16,19 with the time for completion of TMT-A and TMT-B being shorter for persons of higher educational level, but four studies have found that education affects only TMT-B. 15,17,18,20 However, these latter studies included participants with relatively high educational levels only, suggesting that the effects in a population with a relatively low educational level were not fully investigated.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation